(untitled) (Eurasian Journal of Learning and Academic Teaching, 2022)
This article devoted about language. Language is a social practice of meaning making and interpretation, and then it is not enough for language learners just to know grammar and vocabulary. They also need to know how that language is used to create and represent meanings and how to communicate with others and to engage with the communication of others. This requires the development of awareness of the nature of language and its impact on the world